Pharao reelected: Egypt on the road to political pluralism - Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2005)
Egyptian President Hosni Mubarak's reelection on 7 September 2005 came as absolutely no surprise. The only open question was exactly how the vote would split between the president and his strongest opponent, populist liberal opposition leader Ayman Nour. The comfortable official result of 88.6 percent for Mubarak, 7.6 percent for Nour, and not even four percent for the other eight candidates together will allow Mubarak, who is seventy-seven years old and has held the office of president since the assassination of Anwar Sadat in 1981, to govern for another six years - assuming his health holds up. The important point, however, is not the result itself, but the mere fact that for the first time an Egyptian president has been chosen in a contest involving more than one candidate, rather than by referendum. This remains true even though the conditions were so arranged that Mubarak's rivals stood no chance of winning. The election brings about gradual change in the political system by introducing the principle of democ-ratic competition for the office of the supreme decisionmaker for the first time, but the real political effect of this development will not be felt until the Hosni Mubarak era is over.(SWP Comments / SWP)
Keywords: 320